2006
DOI: 10.1016/j.febslet.2006.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing in mosquito salivary glands by RNAi

Abstract: Salivary glands are the ultimate site of development in the insect of mosquito born pathogens such as Plasmodium. Mosquito salivary glands also secrete components involved in anti-haemostatic activities and allergic reactions. We investigated the feasibility of RNAi as a tool for functional analysis of genes expressed in Anopheles gambiae salivary glands. We show that specific gene silencing in salivary glands requires the use of large amounts of dsRNA, condition that differs from those for efficient RNAi in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 21 publications
6
92
0
4
Order By: Relevance
“…Instead they perform complementary functions to optimize successful feeding. Our data and conclusions are supported further by data on the partial silencing of salivary apyrase and gSG6 genes in A. gambiae, which resulted in reduced mosquito feeding efficiency (33,34). Finally, our results support transgenic approaches for studies of gain and loss of salivary functions.…”
Section: Discussionsupporting
confidence: 76%
“…Instead they perform complementary functions to optimize successful feeding. Our data and conclusions are supported further by data on the partial silencing of salivary apyrase and gSG6 genes in A. gambiae, which resulted in reduced mosquito feeding efficiency (33,34). Finally, our results support transgenic approaches for studies of gain and loss of salivary functions.…”
Section: Discussionsupporting
confidence: 76%
“…In other orders such as Diptera, generally higher doses are needed to achieve an effective RNAi response. For example, in the African malaria mosquito, Anopheles gambiae, doses on the order of 1 μg/g to 10 μg/g are necessary to achieve an effective RNAi response (Boisson et al, 2006); and Lepidoptera needs a vast range of concentrations that span from <0.01 μg/g to > 1 μg/g depending on the species (Terenius et al, 2011). Drosophila lack systemic RNAi (Roignant et al, 2003), and therefore are not as sensitive to injection or oral administration of dsRNAs (e.g., most RNAi assays in D. melanogaster are performed with transgenic flies designed to express hairpin RNAs (Dietzl et al, 2007)).…”
Section: Discussionmentioning
confidence: 99%
“…This has been aptly demonstrated in mosquitoes where feeding time has been related to the quantity of apyrase in the glands of different anopheline mosquitoes (Ribeiro et al 1985). More recently, Boisson and colleagues (Boisson et al 2006) confirmed the role of apyrase in efficient mosquito feeding using gene silencing to reduced the expression of the apyrase gene AgApy. Saliva from mosquitoes injected with ds-AgAyp exhibited reduced enzyme activity and was less efficient at inhibiting platelet activity.…”
Section: Changes In Biting and Probing Behaviourmentioning
confidence: 92%